Long-term effect of transurethral partial cystectomy with a 2-micrometer continuous-wave laser for non-muscle-invasive bladder cancer - Lu, Yongliang; Jiang, Sinan; Yin, Xiaotao; Guo, Jiaxiang; Zhu, Xiaoying; Ma, Han; Zhang, Guohui; Yu, Hualiang; Xiao, Yi; Yang, Yong (Frontiers in Surgery, 2023)
Purpose: We have reported the efficacy and safety of 2-micrometer continuous-wave laser cystectomy of non-muscle invasive bladder tumor (NMIBC) (J Urol. 2009;182:66-9). In this study, we evaluated the long-term outcomes of patients with NMIBC who underwent transurethral partial cystectomy with a 2-micrometer continuous-wave laser, and explored the risk factors for tumor recurrence. Methods: This was a retrospective study of patients with NMIBC planned to undergo transurethral partial cystectomy with a 2-micrometer continuous-wave laser at the Fourth Medical Center of the PLA General Hospital between 01/2012 and 12/2014. The primary outcome was bladder cancer recurrence. Results: A total of 75 patients were enrolled. Sixty-two (82.7%) were male. The patients were 59.8±12.9 years of age. The mean operation time was 38.7±20.4 min. No Clavien grade >2 complications occurred. The duration of catheter indwelling was 3.6±1.8 days. The hospital stay was 6.0±2.3 days. The median follow-up was 80 months. A total of 17 patients had a recurrence during follow-up, and the recurrence-free survival (RFS) rate was 77.3%. In the multivariable analysis, the tumor risk group were independently associated with the recurrence of NMIBC (p=0.026). Conclusions: After TURBT with a 2-micrometer continuous-wave laser, RFS was 77.3% at the median follow-up of 80 months. All complications were mild. Only tumor risk group was independently associated with the recurrence of NMIBC.